Efektivitas Asuhan Keperawatan Gigi Keluarga terhadap Kesehatan Gigi dan Status Karies Anak di SDN Center l dan SDN Palleko II - Alfah, Siti; AR, Aisyah; Nurhaedah, Nurhaedah; Hikmah, Nurul; Hidayat, Rahmat (Jurnal Ilmiah Amanah Akademika, 2022)
Family dental health care is a series of activities provided by dental practitioners to help solving dental health problems. This study was aimed to assess family dental care effective ness on changes in dental and oral health as well as caries index of children. This was a quasi-experimental study. There were 23 respondents of SDN Center 1 as the intervention group and 23 respondents of SDN Palleko ll Takalar as the control group, together with their parents. The intervention group was given dental health education and home visit while the control group was not. The results showed no significant difference in knowledge, attitudes, and actions of the children and parents as well as children's dental hygiene status (OHIS) and children's dental caries status (DMF-T) between groups before intervention. After the family dental nursing care was carried out, there were significant differences in knowledge, attitudes, and actions of the children and parents as well as OHIS and DMF-T at three months after the intervention. In conclusion, the knowledge, attitudes, actions of the children and parents as well as the OHIS and DFM-T status were improved after the family dental health care.